Examining Solar PY Mini-Grid System As A Complement To Grid Extension For Rural Electrification With Reference To Yama Community, Northern Ghana. - Abaase, Stephen (2015)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana in partial fulfillment of the requirements for the degree of Master Of Science In Renewable Energy Technologies.